A practical guide for policy analysis : the eightfold path to more effective problem solving - Bardach, Eugene (Sage ;, 2012)
With his original eightfold approach, Bardach encapsulates more than 35 years of teaching students effective, accurate, and persuasive policy analysis. This bestselling handbook presents dozens of concrete tips, interesting case studies, and step-by-step strategies for the budding analyst as well as the seasoned professional. In this new edition, Bardach clarifies some of the book's exposition, paying particular attention to "design problems" and the choice of a "base case." Up-to-date examples, including a new set of environmental problems, make the book even more engaging. Readers will also appreciate a sample document of real world policy analysis, a primer in how to "talk the talk" of policy analysis, and a cheat sheet of strategies for solving a host of policy problems.--Publisher description